Application of lamb waves (ultrasonic waves) in wear detection on aluminium plate / Nik Rosli Abdullah, Shahrul Azam Abdullah and Muhammad Hussain Ismail - Abdullah, Nik Rosli; Abdullah, Shahrul Azam; Ismail, Muhammad Hussain (2006)
Wear is a cause of failure in many engineering components and normally related to the surface roughness of the components surface. The wear rate is high when two rough surfaces are in relative motion compared to the motion involved by two smooth surfaces. Wear can normally be assessed by measuring the depth of wear scar or weighing the component loss. However this method cannot be used when the surface locate inside the machine or if occur on inner part of machine. This work focus on ultrasonic wave's application in order to detect surface roughness which is can relate to the wear phenomenon. Non-destructive Testing is defined as an inspection tool that used to detect internal defect, surface and discontinuities or flaws in materials without destroying their usefulness before it is used in a new design. In this work, there are two method used to detect a surface roughness at the different level of roughness on four specimens made by aluminium alloy. First measurement performs by using stylus profilometer then followed by ultrasonic waves propagation. Comparison between two them was made to draw the relationship of both methods. It is shows strong evidence that ultrasonic waves have a great potential in roughness/wear detection. The time travel from one point to another was recorded for all specimens then calculation of waves velocities show reduction when surface roughness increases. Here we have strong evidence to prove the rough surface absorb energy from waves after propagates through it.